Pengaruh Good Corporate Governance (GCG) terhadap Nilai Perusahaan Saham Syariah Jakarta Islamic Index (JII) - Ready Bagus Prakoso; Hendri Setiawan (Politeknik Raflesia Press, 2025)
— Company value is no less important for a company because the existence of company value brings wealth to shareholders. As the owner of the company, the CEO is responsible for increasing the value of the company so that it can grow. Company values ​​are a reflection of the company's success recognized by management. Good Corporate Governance (GCG) is expected to be able to strive for a balance between various interests that can provide benefits to the company as a whole. The purpose of this study is to determine the Effect of Good Corporate Governance (GCG) on the Value of Jakarta Islamic Index (JII) Sharia Stock Companies. The population in this study was 30 Jakarta Islamic Index (JII) Sharia Stock Companies. While the sample in this study was 13 Jakarta Islamic Index (JII) Sharia Stock Companies. The sampling technique used was Purposive Sampling. The analysis tool used was Multiple Linear Regression. The results of the study showed that institutional ownership had no effect on company value in Jakarta Islamic Index (JII) Sharia Stock Companies for the 2021-2024 Period. Managerial ownership has a negative effect on company value in Jakarta Islamic Index (JII) Sharia Stock Companies for the 2021-2024 Period. Independent board of commissioners has a positive effect on company value in Jakarta Islamic Index (JII) Sharia Stock Companies for the 2021-2024 Period. The audit committee has no effect on company value in Jakarta Islamic Index (JII) Sharia Stock Companies for the 2021-2024 Period.